PENGEMBANGAN SAPI POTONG DI KABUPATEN RAJA AMPAT BERDASARKAN KARAKTERISTIK WILAYAH DAN TERNAK - Rajab Rajab; Mochammad S. Soltief (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
As beef cattle, Bali cattle which rearing by the breeder in Raja Ampat regency most in the traditional extensive system. There are many factors to support beef cattle development in this region such as widely land condition with grass forage and feed concentrate as feed for cattle. The objectives of this study were to identification and analysis beef cattle development in Raja Ampat regency base on region and breed potential. Using survey method by interview to 218 of respondent and field observation were done in Sakabu, Kalobo and Waijan Village which tended as the center of beef cattle breeding. The result showed that beef cattle development reach out for 17,792.55 UT, but in productivity factor, Bali cattle in Raja Ampat was small in body weight. To increase beef cattle production and population can be done by reduced beef productive selling and by using an integrated farming system. Based on the potential of territory, the capability of beef cattle development in Raja Ampat regency can reach 17,792,55 ST, so from that number, the research location is potential to be directed to be the beef cattle development area. However, when viewed from the aspect of productivity, beef cattle are maintained have a lower body weight than other regions, indicating a decrease in performance and genetic quality. Reduction in the number of livestock sales in the population and the application of crop-livestock integration systems can be the solution.